2019
DOI: 10.1186/s12891-019-2641-x
|View full text |Cite
|
Sign up to set email alerts
|

Fourth-generation ceramic-on-ceramic THA results in improvements in midterm outcomes compared to third-generation THA but does not resolve noise problems: a cohort study of a single-hip system

Abstract: Background Using data from the Korean Hip Registry, we aimed to investigate mid-term clinical and radiographic outcomes, including the prevalence of periprosthetic joint infection (PJI), osteolysis, and component loosening or dislocation, and to analyze the incidence of bearing-related complications following modern ceramic-on-ceramic (COC) total hip arthroplasty (THA) using a single cementless hip system. Methods Four hundred eighty-two patients (602 hips) who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…Clicking or squeaking occurred in 22 forte patients and 21 delta patients. There were 9 revisions, and survival rates were 98.4% and 98.6% at 5 years for the forte and delta groups, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clicking or squeaking occurred in 22 forte patients and 21 delta patients. There were 9 revisions, and survival rates were 98.4% and 98.6% at 5 years for the forte and delta groups, respectively [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent long-term meta-analysis showed that improvement of the ceramic over time led to lower fracture rates[ 32 ]. Additionally, in the literature, fourth-generation ceramic bearings showed no ceramic fracture when compared to third-generation CoC[ 33 ]. Since we used a fourth-generation ceramic bearing, this might be a reason that no head or liner fractures occurred in our study[ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were 9 revisions, and survival rates were 98.4% and 98.6% at 5 years for the forte and delta groups, respectively. [37) The reduction in wear rates of CoC bearings when compared to polyethylene have been well documented and the relatively bioinert debris produced from the CoC bearing when compared to polyethylene debris provides the advantage of reducing aseptic loosening due osteolysis [38]. The improvements in the manufacture of ceramic have also shown a reduction in the wear rates with the BIOLOX forte compound showing steady state wear rates of 1.2 mm 3 per million cycles, in contrast to the BIOLOX delta which demonstrated wear rates of only 0.12 mm 3 per million cycles [39].…”
Section: Discussionmentioning
confidence: 99%